2021
DOI: 10.1177/11782218211026651
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic Evaluation of an Adjunctive Yoga Program for Women with Substance Use Disorders in Inpatient Treatment: Within-Treatment Effects on Cravings, Self-efficacy, Psychiatric Symptoms, Impulsivity, and Mindfulness

Abstract: Addiction continues to be a major public health concern, and rates of relapse following currently-available treatments remain high. There is increasing interest in the adjunctive use of mindfulness-based interventions, such as yoga, to improve treatment outcomes. The current study was a preliminary naturalistic investigation of a novel trauma-informed yoga intervention in an inpatient treatment program for women with substance use disorder (SUD). Changes and differences in somatic symptoms, psychiatric symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Two of the randomized controlled trials found no significant differences in treatment, but yoga may contribute to positive, sustainable change at follow-up. Research studies support the potential benefits of adjunctive yoga for women receiving treatment for substance use disorders in both inpatient and community-based settings (Galantino et al, 2021;Petker et al, 2021).…”
Section: Research With Adult Populationsmentioning
confidence: 95%

Mindfulness and Yoga

Arrastia-Chisholm,
Adams,
Cakmakci
et al. 2024
Int. J. PWB
“…Two of the randomized controlled trials found no significant differences in treatment, but yoga may contribute to positive, sustainable change at follow-up. Research studies support the potential benefits of adjunctive yoga for women receiving treatment for substance use disorders in both inpatient and community-based settings (Galantino et al, 2021;Petker et al, 2021).…”
Section: Research With Adult Populationsmentioning
confidence: 95%

Mindfulness and Yoga

Arrastia-Chisholm,
Adams,
Cakmakci
et al. 2024
Int. J. PWB
“…Psychological benefits include improved emotional regulation and cognitive function that enhance a sense of well-being through a calming effect that reduces anxiety, stress, and depression, thus improving mood and relationships 12. Cognitive benefits of yoga include improved attention, memory, body awareness, and emotional awareness 12, 14. Increased acceptance, adaptability, and improved functioning resulting from yoga practice often aid patients in their transition to home.…”
Section: Introductionmentioning
confidence: 99%
“…12 Cognitive benefits of yoga include improved attention, memory, body awareness, and emotional awareness. 12,14 Increased acceptance, adaptability, and improved functioning resulting from yoga practice often aid patients in their transition to home.…”
mentioning
confidence: 99%